Penerimaan Orangtua Kandung Pada Anaknya YangPenyandang Autis - Agustikasari, Dwi (2016)
Parents who have children with autism will initially feel sad, disappointed and can not accept their children because they have high expectations for their children. Parents will also feel confused how to take care of them because of the limitations of knowledge. Parents who can accept their children will do the treatment and care based on the child's condition. The purpose of this study is to describe about the acceptance of the biological parents toward their children's autism. Informants are 2 couples (husband and wife), the choice of informants using purposive sampling with the characteristics of the age 26-40 years, the last education of parent is high school, having a child with autism, the child ages 4-7 years. The results of the study found that both couple can accept their children condition. Mom and Dad acceptance level is different it is influenced by the basic abilities of every child and the amount of children they have. The most influential factors that affect an acceptance are family, religion and society. Both parents quite a role to educate their children as to repeat what has been taught in school, to accompany while treatment and being at home, looking for additional information and sharing with other parents and actively participates in school activities such as seminars held.